ANALISIS SIKAP SOSIAL PADA SISWA KELAS TINGGI MADRASAH IBTIDAIYAH ANWARUL MUSTOFA KECAMATAN KUBU TAHUN 2020 - Imbriti Imbriti; Yuline Yuline; Purwanti Purwanti (Universitas Tanjungpura, 2020)
AbstractThis study contains the Analysis of Social Attitudes in High Class Students of Madrasah Ibtidaiyah Anwarul Mustofa Kacamatan Kubu.2017 / 2018. A common problem in this study is